2019
DOI: 10.1002/jcla.23053
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of long non‐coding RNA intersectin 1‐2 with disease risk, disease severity, inflammation, and prognosis of acute ischemic stroke

Abstract: Background This study aimed to evaluate the predictive value of long non‐coding RNA intersectin 1‐2 (lnc‐ITSN1‐2) for acute ischemic stroke (AIS) risk, and investigate its correlation with disease severity, inflammation, and recurrence‐free survival (RFS) in AIS patients. Methods Three hundred and twenty AIS patients were recruited, and plasma samples were collected within 24 hours after admission. lnc‐ITSN1‐2 expression form plasma was detected by reverse transcription‐quantitative polymerase chain reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…This synergistic effect has been well proved in asthma, airway inflammation, cancer and other autoimmune diseases 80,83 . Although there is no direct evidence showing IL‐17 and IL‐22 are synergistic in promoting stroke, the expression of both IL‐17 and IL‐22 are increased in post‐stroke might provide some counter‐evidence 84,85 . Therefore, the possible synergies between IL‐17 and IL‐22 in stroke need further investigation.…”
Section: Synergistic Effects Of Il‐17a With Il‐6 and Il‐22mentioning
confidence: 99%
“…This synergistic effect has been well proved in asthma, airway inflammation, cancer and other autoimmune diseases 80,83 . Although there is no direct evidence showing IL‐17 and IL‐22 are synergistic in promoting stroke, the expression of both IL‐17 and IL‐22 are increased in post‐stroke might provide some counter‐evidence 84,85 . Therefore, the possible synergies between IL‐17 and IL‐22 in stroke need further investigation.…”
Section: Synergistic Effects Of Il‐17a With Il‐6 and Il‐22mentioning
confidence: 99%
“…One study showed that lnc-ITSN1-2 expression was positively correlated with the National Institutes of Health Stroke Scale (NIHSS) score and reflected the severity of stroke. ( Zhang and Niu 2020 ). Another case study was conducted to investigate the relationship between LncRNA MEG3 and prognostic value.…”
Section: Lncrnas As Potential Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…Thus, MEG3 is a potential marker for diagnosis and prognosis. For prognosis, high lnc-ITSN1-2 expression was correlated with worse Relapse-Free Survival (RFS) in AIS patients ( Zhang and Niu 2020 ). Higher Myocardial infarction associated transcript (MIAT) expression had a relatively poor prognosis.…”
Section: Lncrnas As Potential Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…It is suggested that several lncRNAs might be indicators of disease severity in AIS 16‐18 ; however, no previous study had been conducted to investigate the correlation between lncRNA HULC and disease severity of AIS to the best of our knowledge. In this study, a positive correlation was observed between lncRNA HULC relative expression and NIHSS score in AIS patients, which could be explained by that: (a) the high expression of lncRNA HULC might promote several pro‐inflammatory cytokines such as IL‐6 (mentioned above) to up‐regulate inflammation, which exacerbated the injury of neural cell and increased severity of AIS 19 ; (b) increased lncRNA HULC might promote cell adhesion molecules (such as ICAM1 7 ) to enhance neutrophil infiltration, which resulted in higher levels of vascular dysfunction and thrombosis, 20 thus increasing the severity of AIS; and (c) the up‐regulation of lncRNA HULC might suppress its target miRNAs (such as miR‐9 and miR‐195 6,10 ) to repress the regeneration of neural cells, thus increasing brain injury after stroke.…”
Section: Discussionmentioning
confidence: 99%